2019
DOI: 10.1111/echo.14297
|View full text |Cite
|
Sign up to set email alerts
|

Provocative maneuvers to improve patent foramen ovale detection: A brief review of the literature

Abstract: Patent foramen ovale (PFO) is the most common type of inter‐atrial shunt, with prevalence as high as 30%. Detection of PFO has implications in patients with stroke, peripheral embolism, decompression illness, and other conditions. Transesophageal echo (TEE) with saline contrast injection is the current standard for PFO detection, but even with TEE, PFOs are sometimes missed. With advances in percutaneous PFO closure therapies and proven long‐term benefit of closure, accurate PFO detection takes on cardinal imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…Some practitioners advocate for abdominal compression to improve the Valsalva response and this has been shown to increase the sensitivity of the technique. 54,55 Furthermore, it is not unusual for patients to undertake an exaggerated inspiration immediately prior to the Valsalva and the echo image becomes obscured by inflated lungs. For this reason, it is ideal to instruct the patient to perform the Valsalva after a normal inspiration.…”
Section: Optimisation Of the Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some practitioners advocate for abdominal compression to improve the Valsalva response and this has been shown to increase the sensitivity of the technique. 54,55 Furthermore, it is not unusual for patients to undertake an exaggerated inspiration immediately prior to the Valsalva and the echo image becomes obscured by inflated lungs. For this reason, it is ideal to instruct the patient to perform the Valsalva after a normal inspiration.…”
Section: Optimisation Of the Imagingmentioning
confidence: 99%
“…Using a calibrated device that the patients blows against is ideal, 53 but not always practical. Some practitioners advocate for abdominal compression to improve the Valsalva response and this has been shown to increase the sensitivity of the technique 54,55 . Furthermore, it is not unusual for patients to undertake an exaggerated inspiration immediately prior to the Valsalva and the echo image becomes obscured by inflated lungs.…”
Section: Optimisation Of the Imagingmentioning
confidence: 99%
“…Various studies have shown that other provocative maneuvers, such as abdominal compression, inferior vena cava compression, cough, deep inspiration, and the Müller maneuver, have good results as new provocative maneuvers ( 28 ) ( Table 2 ). At present, the Valsalva maneuver and cough are commonly used in clinical practice, but it can be difficult for patients to cooperate during TEE examination, resulting in difficulty in reaching the standard.…”
Section: Discussionmentioning
confidence: 99%
“…1). In PFO patients, TEE identifies the shunt, spontaneous or under Valsalva maneuver as small, moderate and severe on the basis of an old but still valid classification (Mojadidi et al 2014a;Saver et al 2017;Silvestry et al 2015;Thiagaraj et al 2019;Vitarelli et al 2014 ). The effectiveness of the maneuver can be assessed echocardiographically by the presence of a leftward shift of the primary atrial septum with the release phase, denoting the attainment of RA pressure greater than LA pressure.…”
Section: Diagnostic Methodsmentioning
confidence: 99%